Supply chain management: mergers and acquisitions - Prokop, Darren (Henry Stewart Talks, 2025)
Contractual relationships, Consumer welfare, Horizontal integration, Vertical integration, Antitrust regulations, Foreign direct investment (FDI), The merger paradox, Parent firms, Economies of scale